The Effect of Completeness of Facilities, Quality of Human Resources, and Work Environment Conditions on the Performance of Employees of the Indonesian National Sports Committee of West Papua Province - Indah Murtiyani; Lucia KL Rahaded; Febianus Heatubun (STIE Amkop Makassar, 2024)
This study aimed to analyze the effect of the completeness of facilities, quality of human resources, and work environment conditions on the performance of employees of the Indonesian National Sports Committee of West Papua Province. A quantitative approach with survey techniques was used. Data were collected through questionnaires distributed to 50 KONI West Papua employees selected using purposive sampling. Multiple linear regression analysis identified the effect of independent variables on the dependent variable. The results revealed that the completeness of facilities, quality of human resources, and work environment conditions collectively and individually significantly influenced employee performance. Among the three variables, the quality of human resources had the most dominant influence on improving performance. This study recommends enhancing work facilities, implementing training programs for competency development, and improving work environment conditions to optimize employee performance.